The circular RNA hsa-circ-0072309 plays anti-tumour roles by sponging miR-100 through the deactivation of PI3K/AKT and mTOR pathways in the renal carcinoma cell lines. Issue 1 (4th December 2019) - Chen, Tao; Shao, Shixiu; Li, Wenxian; Liu, Yong; Cao, Yanwei
Abstract: Aims: To explore the roles and regulatory mechanisms of the circular RNA (circRNA)-hsa-circ-0072309 in CAKI-1 and ACHN cells. Methods: CAKI-1 and ACHN cells were transfected with hsa-circ-0072309 overproduction vector (circRNA) and microRNA-100 (miR-100) mimic or the corresponding controls. Cell viability was detected with the CCK-8. The protein expression levels of p53, c-Myc, cleaved-caspase-3/9, matrix metalloproteinase (MMP)-2/9, vimentin, AKT, PI3K and mTOR were individually determined through western blot. qRT-PCR was used to examine the expressions of hsa-circ-0072309 and miR-100. The apoptotic rate and the migration or invasion rates were separately determined by the annexin v-FITC/PI with a flow cytometer and modified two-chamber migration assay or millicell hanging cell culture. Results: The hsa-circ-0072309 was poorly expressed in tumor tissue. Abundant hsa-circ-0072309 induced the inhibitions of cell proliferation, migration and invasion, as well as the PI3K/AKT and the mTOR cascades but enhancement of apoptosis. circRNA stimulated the down-regulation of miR-100, which was low-expressed in tumour tissue and whose overproduction abolished the impacts of circRNA on these elements mentioned above. Conclusion: The hsa-circ-0072309 played anti-tumour roles by targeting miR-100 by blocking the PI3K/AKT and mTOR cascades in the CAKI-1 and ACHN cell lines.